Data processing section for microprocessor-like integrated circuits - Susin, Altamiro Amadeu (2011)
A methodology for the design of complex logic VLSI circuits is presented. The target application is deseribed by an algorithm from which the structures of the control section and the data processing section of the integrated circuit are inferred. The Srchltectural aspects are discussed and a model is proposed. A set of functional cells is then presented which implements the data section.